2016
DOI: 10.1038/ncomms11085
|View full text |Cite
|
Sign up to set email alerts
|

Rotational manipulation of single cells and organisms using acoustic waves

Abstract: The precise rotational manipulation of single cells or organisms is invaluable to many applications in biology, chemistry, physics and medicine. In this article, we describe an acoustic-based, on-chip manipulation method that can rotate single microparticles, cells and organisms. To achieve this, we trapped microbubbles within predefined sidewall microcavities inside a microchannel. In an acoustic field, trapped microbubbles were driven into oscillatory motion generating steady microvortices which were utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
278
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 421 publications
(283 citation statements)
references
References 71 publications
4
278
0
1
Order By: Relevance
“…[147][148][149] The acoustic technique has three merits: (a) the capability of manipulating most microparticles, regardless of optical, electrical, magnetic, or shape properties; (b) the ability to manipulate objects with a range of scales, from nanometer to millimeter; and (c) the capability of rapidly manipulating a single particle or groups of particles.…”
Section: E Acoustic Trapsmentioning
confidence: 99%
“…[147][148][149] The acoustic technique has three merits: (a) the capability of manipulating most microparticles, regardless of optical, electrical, magnetic, or shape properties; (b) the ability to manipulate objects with a range of scales, from nanometer to millimeter; and (c) the capability of rapidly manipulating a single particle or groups of particles.…”
Section: E Acoustic Trapsmentioning
confidence: 99%
“…However, the integration of different on‐chip units into an all‐in‐one, fully functional µFACS remains challenging due to their complex designs or incompatibility for integration. Among the various microfluidic techniques for FACS, acoustofluidics (i.e., the fusion of acoustics and microfluidics) is well recognized because of its amenability to integration, miniaturization, and biocompatibility . For example, Jakobsson et al demonstrated an acoustofluidic FACS that uses bulk acoustic waves (BAW) for both cell focusing and cell deflection, and achieved a throughput of ≈150 events s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…As a noninvasive and noncontact manipulation method, acoustic trapping has the advantage that it is able to simply levitate many kinds of objects from small living animal to bacteria 15, 16, 17, 18, 19, 20, 21. More importantly, the penetration of sound wave is much deeper than light in nontransparent media.…”
Section: Introductionmentioning
confidence: 99%